Outcomes of osseointegrated implants in patients with benign and malignant pathologies of the head and neck: a 10-year single-centre study. Issue 10 (October 2021) - Khadembaschi, D.; Borgna, S.C.; Beech, N.; Batstone, M.D.
Abstract: The surgical management of head and neck pathologies involving the maxilla and mandible results in significant functional and aesthetic deficits, and ultimately reduced quality of life. Composite free flaps used for reconstruction address many of these deficits and create a foundation for the use of osseointegrated implants to support prosthetic replacement of the dentition. There are few comparative studies examining outcomes of implants in native and reconstructed bone in head and neck cancer patients. The aim of this retrospective cohort study was to compare survival rates and the effects of risk factors between implants placed in native and reconstructed bone. The Kaplan–Meier method estimated cumulative 1- and 5-year implant survival rates of 99.5% and 95% for native bone and 96% and 88% for reconstructed bone. Multivariate Cox regression found an increased risk of implant failure in reconstructed bone (hazard ratio (HR) 9.9, 95% confidence interval (CI) 3.4–29.7, P  < 0.001). Subgroup analysis of the cohorts found an increased risk of failure in the reconstructed group associated with radiotherapy (HR 6.4, 95% CI 1.8–22.3, P  = 0.004), current smoking (HR 23.2, 95% CI 2.7–198.6, P  = 0.004), and previous smoking (HR 9.0, 95% CI 1.1–71.9, P  = 0.038). There was no effect in the native bone group. Implants placed into reconstructed bone had higher rates of failure, and smoking status and radiotherapy increased the risk of implant failure.